TEACHING WRITING DESCRIPTIVE TEXTS USING FOUR SQUARE WRITING METHOD (FSWM) - Setiawati, Ghinna Dini; Sudarsono, Sudarsono; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of the study was to find out whether using Four Square Writing Method in teaching writing descriptive is effective. The form of this research was a pre-experimental study. The population of this research was the Year-10 students of SMA Negeri 8 Pontianak in academic year 2018/2019. By using cluster random sampling, the researcher took one class as the sample of this study. The sample was 35 students of X MIPA 1. The data were collected through written test. Before analyzing the data using t-test formula, the students’ test results were graded based on the scoring scale. In accordance to the findings of this study, it showed the significant effectiveness in students’ writing ability taught by using Four Square Writing Method. The obtained t-value (15.40) was higher than the critical r value (1.961) by the degree of freedom 33. It was inferred that Four Square Writing Method affects students’ descriptive writing ability significantly. Keywords: Descriptive Texts, Four Square Writing Technique, Writing